IDENTIFICATION OF SUITABLE VARIETIES FOR SEED PRODUCTION OF JUTE IN NON-TRADITIONAL AREAS OF BANGLADESH - Al-Mamun, M.; Saha, C. K.; Mostofa, M. G.; Miah, A.; Hossain, M. Z. (Bangladesh Journal of Plant Breeding and Genetics, 2017)
The experiment was conducted at Hill Agricultural Research Station, Khagrachari (representing hilly areas), Agricultural Research Station, Satkhira and Jute Research Station, Patuakhali (representing saline areas) with seven varieties of jute and one variety of kenaf to find out the seed production potentiality in non-traditional areas. All varieties were sown in late July to mid August in 2009 to 2011. At hilly station white jute varieties (BJRI Deshi Pat-6, CVL-1 and BJRI Deshi Pat-5) performed better for seed production than tossa jute and kenaf varieties. At saline station (both Satkhira and Patuakhali) kenaf variety HC-95 performed better for seed yield than white and tossa jute varieties (O-9897, OM-1, BJRI Tossa Pat-4 and BJRI Tossa Pat-5). The kenaf variety (HC-95) produced the highest yield (0.86 ton/ha) in saline areas. Among the white jute varieties, BJRI Deshi Pat-5 gave the highest yield (0.66 ton/ha) and in case of tossa jute varieties, BJRI Tossa Pat-5 gave the highest seed yield (0.70 ton/ha). Therefore, BJRI Deshi Pat-5 of white jute, BJRI Tossa Pat-5 and HC-95 of kenaf are considered as the best varieties for seed production in hilly and saline areas of Bangladesh, respectively.